2009
DOI: 10.1111/j.1439-0531.2008.01117.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of Boar Gonad Development, Spermatogenesis with regard to Semen Characteristics, Libido and Serum Testosterone Levels based on large White Duroc × Chinese Erhualian Crossbred Boars

Abstract: Chinese Erhualian pigs are known for prolificacy with distinct reproductive traits compared with Western commercial breeds. In this study, a four-generation intercross resource population was constructed using White Duroc boars and Chinese Erhualian sows as founder animals, and a total of 14 male reproductive traits were recorded in 411 F2/F3 boars including the testis and epididymis weights, the seminiferous tubular diameter and spermatogenesis at 60, 90 and 300 days of age, semen characteristics, serum testo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 28 publications
2
22
1
4
Order By: Relevance
“…These observations agree with results obtained in studies with large White Duroc × Chinese Erhualian Crossbred boars at three developmental stages, where the testosterone concentration correlated with epididymis weight and libido scores, although libido and serum testosterone level were not correlated with sperm production [22]. …”
Section: Discussionsupporting
confidence: 90%
“…These observations agree with results obtained in studies with large White Duroc × Chinese Erhualian Crossbred boars at three developmental stages, where the testosterone concentration correlated with epididymis weight and libido scores, although libido and serum testosterone level were not correlated with sperm production [22]. …”
Section: Discussionsupporting
confidence: 90%
“…With increasing age, the correlation dependence between these parameters grew and in the category of 37 to 48 months it reached the value of 0.65 for CO/NOT and 0.63 for CO/NOC) (p < 0.05). High correlation (0.73) between these parameters reported Ren et al (2009). A very weak negative correlation (-0.13 to -0.19) (p < 0.05) was found between the motility of spermatozoa and the percentage of abnormal spermatozoa throughout the age categories, which is contrary to the conclusions of the Wolf (2010), who found that the correlation coefficient between these parameters was at level -0.57.…”
Section: Resultscontrasting
confidence: 54%
“…In recent years, AI has been widely implemented in the production of pigs. Therefore, the choice of boars is becoming increasingly important and urgent to the pig industry (Ren et al, 2009). Understanding the basic genetic differences between the male reproductive traits of different breeds of boars is necessary to increase the efficiency of sperm production in insemination stations (Safranski, 2008).…”
Section: Introductionmentioning
confidence: 99%